Pacing strategy during simulated mountain bike racing - Ferreira Viana, B.; Oliveira Pires, F.; Inoue, A.; Meireles Santos, T. (International Journal of Sports Physiology and Performance, 2018)
Cross-country mountain biking (XCO) is a popular high-intensity endurance cycling event, but XCO pacing strategy has not been fully examined. This study examined the pacing strategies of different XCO athletes during a laboratory-simulated XCO performance test. Brazilian cyclists classified as performance-cohort level 3 performed an XCO race simulation. The simulation consisted of four 10-km laps with a gradient of 0-10%. No group-vs-time interaction was found in lap time (P=.169), absolute (P=.719) and relative (P=.607) power output, ratings of perceived exertion (P=.182), or heart rate (P=.125). There was a time main effect, as athletes decreased power output by 0.3 W/kg throughout the XCO simulation, thereby resulting in a 1.6-min decrement per lap. The power output corresponding to the onset of blood lactate accumulation adequately represented the mean power of the first lap. These results showed that 2 groups of cyclists with different training status adopted similar pacing strategies during an XCO race simulation, as they both used a fast-starting pacing strategy followed by positive pacing that resulted in a linear decrease in power output at every lap.